Hyperacute treatment of childhood stroke in Lyme neuroborreliosis: report of two cases and systematic review of the literature. (June 2022) - Philipps, Joerg; Erdlenbruch, Bernhard; Kuschnerow, Michael; Jagoda, Sunil; Salihaj, Blerta; Glahn, Joerg; Schellinger, Peter Dieter
The safety and efficacy of hyperacute reperfusion therapies in childhood stroke due to focal cerebral arteriopathy (FCA) with an infectious and inflammatory component is unknown. Lyme neuroborreliosis (LNB) is reported as a rare cause of childhood stroke. Intravenous thrombolysis (IVT) and endovascular therapy (EVT) have not been reported in LNB-associated stroke in children. We report two children with acute stroke associated with LNB who underwent hyperacute stroke treatment. A systematic review of the literature was performed to identify case reports of LNB-associated childhood stroke over the last 20 years. Patient 1 received IVT within 73 min after onset of acute hemiparesis and dysarthria; medulla oblongata infarctions were diagnosed on magnetic resonance imaging (MRI). Patient 2 received successful EVT 6.5 hr after onset of progressive tetraparesis, coma, and decerebrate posturing caused by basilar artery occlusion with bilateral pontomesencephalic infarctions. Both patients exhibited a lymphocytic cerebrospinal fluid (CSF) pleocytosis and elevated antibody index (AI) to Borrelia burgdorferi . Antibiotic treatment, steroids, and platelet inhibitors including tirofiban infusion in patient 2 were administered. No side effects were observed. On follow-up, patient 1 showed good recovery and patient 2 was asymptomatic. In the literature, 12 cases of LNB-associated childhood stroke were reported. LNB-associated infectious and inflammatory FCA is not a medical contraindication for reperfusion therapies in acute childhood stroke. Steroids are discussed controversially in inflammatory FCA due to LNB. Intensified antiplatelet regimes may be considered; secondary prophylaxis with acetyl-salicylic acid (ASA) is recommended because of a high risk of early stroke recurrence.